Avaliação da diferença de potencial elétrico do tubo de raios X em equipamentos de radiologia convencional e mamografia - Griebler, Cristian Felipe (2020)
The evaluation of the potential difference of X-ray equipment is a fundamental item in the quality control program of a radiodiagnosis clinic. This evaluation is important to ensure the patient’s radiological protection and to guarantee the quality of the exam image. The image quality is responsible for the correct diagnosis of the exam. National standards, Portaria 453/98 and the recent RDC 330/19, establish different operating limits for the voltage produced by the equipment’s X-ray tube and do not present a clear definition for the term voltage. The objective of this work was to evaluate the performance of three X-ray equipments and three mammographic equipments through the tests of accuracy and reproducibility established in the national standard. Mean peak voltage, practical peak voltage and maximum peak voltage were measured by the Accu-Gold AGMS-D and AGMS-M sensors, and the values provided by the Accu-Gold Radcal software. The voltage values evaluated for the six devices were within the tolerance limits established in the standard for the accuracy and reproducibility tests. Accuracy tests, among conventional X-ray equipment, showed deviations from 0.16 to 6.25% compared to the nominal voltage. Among mammography equipments, the deviations were from 0.33 to 3.2% to the nominal voltage. Reproducibility tests, among conventional X-ray equipment, showed deviations of 0.11 to 0.82% compared to the nominal voltage. Among mammography equipments, the deviations were 0.3 to 0.5 kV and the coefficient of variation (CV) was less than 0.02. In this work, the importance of quality control tests and the need for multiprofessional colaboration were verified. It is concluded that, in parallel to the quality control tests, multiprofessional performance is an essential practice to guarantee the quality of the radiodiagnostic exam.